2021
DOI: 10.3390/min11050448
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Orthorhombic α-Calcium Formate from Sediments of Alkali Lake, Oregon, USA

Abstract: Centimeter-sized crystals of orthorhombic calcium formate, α-Ca(HCO2)2 from Alkali Lake, Oregon, USA have been studied by means of powder and single-crystal X-ray diffraction analysis, infrared, and Raman spectroscopy. Based on the data on carbon isotope abundance in calcium formate and associated minerals, it was concluded that the formation of α-Ca(HCO2)2 may be a result of a combination of two factors: lake microbial metabolism and anthropogenic pollution with Agent Orange. Possible causes of stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Importantly, the 1356 and 1392 peaks, as well as the 2800 and 2900 peaks, are all co-localized over the same area on the map. This suggests that this area corresponds to Ca­(HCOO) 2 formation as previous studies have shown that FA adsorption on HAP (010) occurs through the transfer of the acidic proton on FA to the surface and HCO – bonding to the surface Ca site. ,, Since the confocal Raman analysis depth is several hundred nanometers into the crystal, HAP parent structure peaks were detected in the areas where Ca­(HCOO) 2 was detected, as shown in the combined images. Raman mapping indicates the formation of Ca­(HCOO) 2 on the HAP particles but localized to distinct parts of the HAP particles.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Importantly, the 1356 and 1392 peaks, as well as the 2800 and 2900 peaks, are all co-localized over the same area on the map. This suggests that this area corresponds to Ca­(HCOO) 2 formation as previous studies have shown that FA adsorption on HAP (010) occurs through the transfer of the acidic proton on FA to the surface and HCO – bonding to the surface Ca site. ,, Since the confocal Raman analysis depth is several hundred nanometers into the crystal, HAP parent structure peaks were detected in the areas where Ca­(HCOO) 2 was detected, as shown in the combined images. Raman mapping indicates the formation of Ca­(HCOO) 2 on the HAP particles but localized to distinct parts of the HAP particles.…”
Section: Resultssupporting
confidence: 58%
“…In the case of FA-modified HAP, additional peaks at 1356, 1392, 2880, and 2900 cm –1 were observed. These peaks are attributed to the formation of Ca­(HCOO) 2 as the FA vapor reacts with HAP and exhibits new C–H and C–O stretching modes. , …”
Section: Resultsmentioning
confidence: 99%
“…This effect is well observed in Figure b, in which the vibrations of C–O and C–H bonds at 1354 and 1380 cm –1 are shifted toward higher frequencies in the presence of calcite dissolution (1355 and 1386 cm –1 , respectively). This behavior can be associated with the differences in the cation sizes and their coordination numbers over the vibrational modes of the FM molecule, affecting the Ca 2+ –O and Na–O bond lengths and allowing a certain degree of distortion. , Thus, it is evident that the interaction between FM and Ca 2+ to produce calcium biformate by the ion exchange reaction led to an enhanced level of calcite dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior can be associated with the differences in the cation sizes and their coordination numbers over the vibrational modes of the FM molecule, affecting the Ca 2+ −O and Na−O bond lengths and allowing a certain degree of distortion. 66,67 Thus, it is evident that the interaction between FM and Ca 2+ to produce calcium biformate by the ion exchange reaction led to an enhanced level of calcite dissolution.…”
Section: Resultsmentioning
confidence: 99%